PERANAN DAN SUMBANGAN MUHAMMAD B. ’UMAR AL-WAQIDI DALAM BIDANG PENSEJARAHAN ISLAM - Mujani, Wan Kamal (Journal of Al-Tamaddun, 2010)
Muhammad b. ’Umar al-Waqidi (130-207H/747-822M) was a Medinan historian and was famous in the field of Sirah and Maghazi. His scholarly can be seen through his abundant and precious works which most of them related to the history. al-Waqidi’s master piece i.e. Kitab al-Maghazi discusses about Saraya and Ghazawat during the days of Rasulullah P.B.U.H. in Medina. It was his genuine work and no element of plagiarism as alleged by some of the orientalists. al-Waqidi was reported to derive his facts of writing from the autoritative sources. When he writes on Ghazwah, he will go the the place where the Ghazwah occurred and observes it. These were among of the factors which gave him more validity in historiography compared to another historians. Futhermore, his writing was based on the chronology and the dates were mentioned in every event. Besides, he also uses simple words and there are geographical explanations in his writing. Until now, Kitab al-Maghazi remains as the main source for Saraya and Ghazawat which took place during the Muhammad P.B.U.H. period. Eventhough, some of the Muhaddithun questioned the the autoritative of al-Waqidi, his role and contribution in early Islamic historiograph is undisputible.